Sleep to lower elevated blood pressure: a randomized controlled trial (SLEPT) - McGrath, E; Espie, C; Power, A; Murphy, A; Newell, J; Kelly, C; Duffy, N; Gunning, P; Gibson, I; Bostock, S; O'Donnell, M (Oxford University Press, 2017)
Impaired sleep quality is common and associated with an increased risk of cardiovascular disease (CVD), thought to be mediated through adverse effects on established vascular risk factors, particularly hypertension. We determined if a web-delivered sleep intervention (sleep-hygiene education, stimulus control, and cognitive behavioral therapy) reduces blood pressure compared to vascular risk factor education (standard care) alone.Phase II randomized, blinded, controlled trial of 134 participants without CVD with mild sleep impairment and blood pressure 130-160/<110 mm Hg. The primary outcome was the difference in the mean change in 24-hour ambulatory systolic blood pressure (SBP) over 8 weeks between intervention and control groups. Secondary outcomes included measures of sleep quality and psychosocial health, namely Insomnia Severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI).Participants in the sleep intervention group showed significantly greater improvements in sleep quality, including ISI [difference in mean improvement 2.8; 95% confidence interval (CI), 1.3-4.4], PSQI (1.1; 95% CI, 0.1-2.2), sleep condition indicator (0.8; 95% CI, 0.2-1.4), and psychosocial health, including BDI (2.0; 95% CI, 0.3-3.7) and BAI (1.4; 95% CI, 0.02-2.8). The mean improvement in 24-hour ambulatory SBP did not differ between the sleep intervention (0.9 mm Hg) and control (0.8 mm Hg) arms, (difference in mean improvement 0.1; 95% CI, -3.4 to 3.2).A simple, low-cost, web-delivered sleep intervention is feasible and significantly improves sleep quality and measures of psychosocial health in individuals with mild sleep impairment but does not result in short-term improvements in blood pressure.